The solution of the given system of linear equations is:
x=-2, y=-6
Step-by-step explanation:
Given
[tex]y=-3x-12\ \ \ \ Eqn\ 1\\-6x+4y=-12\ \ \ \ Eqn\ 2\\Put\ y=-3x-12\ in\ Eqn\ 2\\-6x+4(-3x-12)=-12\\-6x-12x-48=-12\\-18x=-12+48\\-18x=36\\Dividing\ both\ sides\ by\ -18\\\frac{-18x}{-18}=\frac{36}{-18}\\x=-2\\Putting\ x=-2\ in\ Eqn\ 1\\y=-3(-2)-12\\y=6-12\\y=-6[/tex]
Hence,
The solution of the given system of linear equations is:
x=-2, y=-6
Keywords: Linear Equations, Variables
Learn more about linear equations at:
#LearnwithBrainly